Pengabdian Masyarakat dengan “Penyuluhan Nutrisi pada Lansia” di Posyandu Seruni 11 Wilayah Kerja Puskesmas Tondano Kota Pekalongan - Ana Setyowati; Ni’matul Ulya (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Elderly (elderly) is a stage of life in which a person experiences a decline in body function, both physically, mentally, and socially. These changes impact the body's ability to digest and absorb nutrients, so that the elderly are at risk of experiencing various nutritional problems. Decreased food intake can cause nutritional deficiencies, which result in impaired health status and general problems associated with aging. The purpose of this community service is to increase the knowledge and awareness of the elderly about the importance of fulfilling a balanced diet in maintaining health, preventing disease and maintaining quality of life in old age. The method used in this community service activity began with an opening and introduction of the speakers, then continued with the delivery of health education materials, a question and answer session with participants and finally a closing. Through this activity there is an increase in the elderly's knowledge about the importance of balanced nutrition and encourages the elderly to be more concerned with diet, fluid intake and healthy lifestyle habits.